Kusmana C, Hidayat T, Istomo, Rusdiana O. 2018. Growth performance of Bruguiera gymnorrhiza derived from cut-propagule seedling. Biodiversitas 19: 208-214. The availability and existence of Bruguiera gymnorrhiza seed sources is getting decreased. This cau - CECEP KUSMANA; TOPIK HIDAYAT; ISTOMO ISTOMO; OMO RUSDIANA (Society for Indonesian Biodiversity, 2018)
Kusmana C, Hidayat T, Istomo, Rusdiana O. 2018. Growth performance of Bruguiera gymnorrhiza derived from cut-propagule seedling. Biodiversitas 19: 208-214. The availability and existence of Bruguiera gymnorrhiza seed sources is getting decreased. This causes the generative reproduction of this plant is limited. The present research was carried out to study the growth performance of B. gymnorrhiza derived from vegetative cut-propagule seedling by employing different type of cut-propagule, the provision of root promoting hormones, and the provision of NPK fertilizer. The research was conducted at the Greenhouse for 6 months using a completely randomized design (CRD) 3x3x2 factorial with five replications. The results showed that B. gymnorrhiza could be propagated by cut-propagule. Seedlings growth which derived from complete propagule apparently had a better performance than those derived from cut-propagule. Roots derived from complete propagule and the bottom part of cut-propagule grow faster than the top part of cut-propagule. Two types of shoot such as shoot existing before planting which was derived from complete propagule and top part of cut-propagule; and shoots existing after planting called as adventitious shoot derived from the bottom part of cut-propagule has been formed. Unfortunately, new complete shoots derived from the bottom part of cut-propagule was not formed. Furthermore, there was no significant effect of root promoting hormone and NPK fertilizer induction on the shoot and root growth of B. gymnorrhiza.